The Influence of Agile Leadership, Rewards and Career Development on Employee Performance - Yafda Santany; Kartika Sari Lubis (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to identify and analyze the influence of Agile Leadership, Rewards, and Career Development on Employee Performance at the National Amil Zakat Agency (BAZNAS) of North Sumatra Province. Methodology/approach – The research employed a quantitative approach with an associative research method. The population consisted of all 31 employees of BAZNAS North Sumatra Province, and the sampling technique used was non-probability sampling. Data were collected through questionnaires distributed to all employees. Findings – The results indicate that Agile Leadership does not have a significant effect on employee performance, while Rewards and Career Development each have a positive and significant effect. Simultaneously, the three variables significantly influence employee performance. The adjusted R-square value of 0.880 shows that 88% of performance variation can be explained by these variables. Novelty/value – This research highlights the importance of reward and career development systems in enhancing employee performance in nonprofit organizations such as BAZNAS.